SISTEM INFORMASI PENJUALAN KACAMATA DAN AKSESORIS BERBASIS WEB PADA TOKO OPTIK HENDRY - Shidqi Azmi Fadhil (2023)
Hendry Optics is one of the optical spectacles that offers various kinds of glasses, eyeglass cases, lenses, frames, eyeglass cleaners, contact lenses and other optical accessories. In current sales practices, Hendry Optics is still conventional, that is, if a buyer wants to buy an optical device at Hendry Optics, they have to go directly to the shop to buy it. In connection with these conditions, the problem is that many consumers do not have enough time to come to the store because they are busy with work or other things. In addition, data processing still uses a konvensional system, which is written in a ledger. This causes the possibility of unclear sales data due to writing that is illegible, damaged or lost. In connection with these problems, Hendry Optics created a web-based sales information system so that customers from remote places don't have to come to the store. Only by visiting the website, customers can make purchases online and data processing can be completed computerized. The language used to build this system is PHP and the database used is MySQL. The method used in system design is the waterfall method. The results of this study are that a web-based sales information system can be a solution to simplify and speed up the transaction process, promote products, make data search easier, and make reports easier, thus increasing the number of sales and displaying information on goods sold at Hendry Optics.